O Desenvolvimento dos Municípios Nordestinos Dedicados à Cotonicultura em Diferentes Paradigmas Produtivos no Período 2000-2010 - Paulo Thiago Nunes Bezerra de Melo (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2019)
The aim of this article is to compare the Northeastern municipalities dedicated to conventional and organic cotton farming from the changes in their development indicators in the period from 2000 to 2010. From the discussion on cotoniculture in Northeast of Brazil, the theoretical contribution presented in this article lays on the understanding that the different paradigms in rural areas, conventional and organic, promote distinct results in the development process. Conventional and organic cotoniculture can promote distinct sets of economic, sociocultural and ecological outputs that provide the basis for a sustainable development process in rural areas. The present study is a descriptive one in nature and adopts a quantitative approach in data collection and analysis. Secondary data were collected on GDP, HDI and the number of households with durable goods in the analyzed municipalities. This study adopts a comparative approach in the results analysis. The development of municipalities dedicated to conventional cotoniculture has shown a stronger orientation for the sustainable development model than the municipalities dedicated to organic cotton production.